Mitochondrial Cytochrome c Oxidase Subunit 1 Sequence Variation in Prostate Cancer - Takara A. Scott; Rebecca S. Arnold; John A. Petros (Scientifica)
Purpose. Mitochondrial DNA (mtDNA) mutations have been described in every adult neoplasm including prostate cancer. There are marked racial differences in mutations within the cytochrome c oxidase subunit 1 (COI) gene in individuals with prostate cancer (PCa). The purpose of this study was to identify the variation in COI gene sequence in African and Caucasian Americans with prostate cancer. Methods. We sequenced the COI gene from peripheral blood in 482 prostate cancer patients and 189 controls. All bases that differed from the revised Cambridge Reference Sequence (rCRS) were classified as either silent or missense and the compiled alterations were then compared between races and published reports. Results and Conclusions. We found inherited mtDNA COI missense variants in 8.8% of Caucasian prostate cancer patients (vs. 0.0% controls) and 72.8% of African-American prostate cancer patients (vs. 64.3% controls) A total of 144 COI variants were identified, of which 30 were missense mutations. Of 482 PCa patients, 116 (24.1%) had one or more missense mutations. Further evaluation of this gene and these mutations may allow for the identification of genetically at-risk populations. The high rate of COI mutations in African-Americans may account for some of the racial disparity observed in prostate cancer.